MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DENGAN PEMANFAATAN MEDIA QUIZIZZ PADA SISWA KELAS 5 SDN WONOSARI 2 - Wiwik Ratnawati; Raras Setyo Retno; Nugrahaning Triastuti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
By using Quizizz media and a problem-based learning model, this study aims to improve the mathematics learning outcomes of fifth grade students of SDN Wonosari 2. A classroom action research design with a structured action cycle was used in this study. V grade students of SDN Wonosari 2 in the second semester of the 2022/23 school year were the subject of this study. Student learning outcomes in mathematics are the focus of this study. While the instrument used for data collection is a math learning outcomes evaluation test. Descriptive analysis is the method of data analysis. The average value of mathematics learning achievement at least KKM = 75 with 85 percent completeness is the benchmark for the success of this study. The results obtained from this study are before being given action or pre-cycle the average math learning outcomes of 56.25 and only 5 students or 31.25% are complete. In cycle I it increased, the average student math learning outcomes were 70 and there were 8 students or 50% who completed learning math. While in cycle II, the average student learning outcomes reached 86.25 and there were 14 students or 87.5% who completed learning mathematics. This study shows that using the Problem Based Learning learning model using Quizizz media can improve the learning outcomes of mathematics data collection and presentation material.